Предмет: Алгебра,
автор: Анеличка27
помогите срочно надо
Приложения:
![](https://files.topotvet.com/i/132/13236f4203258ff738bb52f0e5f1bca8.jpg)
Ответы
Автор ответа:
0
ОЗ (x-1)(x+1)≠0⇒x≠1,x≠-1
6-2(x+1)=2(x²-1)-(x+4)(x-1)
6-2x-2=2x²-2-x²+x-4x+4
x²-3x+2+2x-4=0
x²-x-2=0
x1+x2=1 U x1*x2=-2
x1=-1 не удов усл
x2=2
6-2(x+1)=2(x²-1)-(x+4)(x-1)
6-2x-2=2x²-2-x²+x-4x+4
x²-3x+2+2x-4=0
x²-x-2=0
x1+x2=1 U x1*x2=-2
x1=-1 не удов усл
x2=2
Похожие вопросы
Предмет: Українська мова,
автор: mnnhffiyfvbjjb
Предмет: Английский язык,
автор: sasastahova398
Предмет: Геометрия,
автор: hhhgeorgij
Предмет: Информатика,
автор: alexlev659